Bilingualisme dan Multilingualisme: Pro dan Kontra pada Perkembangan Bahasa dan Kognitif Anak - Niswatin Nurul Hidayati (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract, language has a central role in human life because of its function as a communication tool. Mastering a variety of languages can be said to have many advantages because humans can expand our access to the outside world, as well as update more external knowledge. That reason could be the one that underlies the phenomenon of bilingualism and multilingualism around us. So, parents begin to introduce foreign languages to their children early on, especially English. Educational Institutions ranging from kindergartens and elementary schools to even colleges teach students and students to the international language. Not infrequently, parents put their children into tutoring institutions so that children are able to begin to recognize and master foreign languages early on, others use them as a means of communication at home. However, it turns out there are pros and cons to the phenomenon of bilingualism and multilingualism among experts and also society in relation to language and cognitive development in children. The pros say that bilingual or multilingual children are better than monolingual ones, for example in mastering vocabulary, understanding other people's cultures so that they are more tolerant of differences, and have better test results on verbal tests. However, the contra party mentioned that there are losses experienced by bilingual or multilingual children, where the child's brain works very hard and has a high burden and has a slow ability to master language. This short article discusses the pros and cons that occurred based on the results of several studies conducted by experts. Keywords: bilingualism, multilingualism, language development, cognitivedevelopment, children